Femoral head–neck offset in the Indian population: A CT based study - Malhotra, Rajesh (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Femoroacetabular impingement has been postulated as the important cause of primary osteoarthritis in non dysplastic hips. We postulated that the rarity of primary osteoarthritis of hip in Indian population could be attributable to morphological differences, specifically to a lower prevalence of abnormal head–neck morphology. We conducted an anthropometric study to evaluate the prevalence of abnormal head–neck offset in Indian population and to correlate it with the low prevalence of primary osteoarthrosis in the Indian population. MATERIALS AND METHODS: The computed tomography (CT) images of 85 apparently normal hips were analysed. An axial image was created parallel to the central axis of the femoral neck and passing through the center of the femoral head using coronal scout view. This image was then used to calculate alpha and beta angles and the head–neck offset ratio. The measurements were made by two independent observers on two different occasions. RESULTS: The prevalence of abnormal head–neck offset ratio was 11.7% and the mean alpha and beta angles were 45.6° and 40.6°, respectively. Pearson correlation coefficients for intra-observer and inter-observer agreement were, respectively, 0.84 and 0.80 for alpha angle, 0.80 and 0.77 for beta angle and 0.78 and 0.75 for head–neck offset ratio. The values were similar to those reported in the western population. CONCLUSION: The differences in the prevalence of hip osteoarthritis in Indian and western populations are not attributable to variation in the prevalence of abnormal head–neck offset.